2019
DOI: 10.1016/j.ophtha.2018.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Association between Rates of Visual Field Progression and Intraocular Pressure Measurements Obtained by Different Tonometers

Abstract: Mean ORA IOP was more predictive of rates of visual field loss than mean IOP obtained by GAT or RBT. By correcting for corneal-induced artifacts, IOPcc measurements may present significant advantages for predicting clinically relevant outcomes in patients with glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Second, it is possible that the Icare IC-100 model gives systematically lower IOP measurements than GAT which is the reference standard for measurement of IOP. This bias towards lower IOP readings with this Icare model has also been observed in two other recent studies 41 42. It was emphasised to all participants that an IOP below our referral threshold did not necessarily mean that they did not have glaucoma.…”
Section: Discussionsupporting
confidence: 82%
“…Second, it is possible that the Icare IC-100 model gives systematically lower IOP measurements than GAT which is the reference standard for measurement of IOP. This bias towards lower IOP readings with this Icare model has also been observed in two other recent studies 41 42. It was emphasised to all participants that an IOP below our referral threshold did not necessarily mean that they did not have glaucoma.…”
Section: Discussionsupporting
confidence: 82%
“…18,19 IOPcc is regarded as being better able to predict clinically relevant outcomes than conventional IOP measurement. 20…”
Section: Measurement Of Corneal Biomechanical Propertiesmentioning
confidence: 99%
“…Ultimately, the measure of IOP that best predicts who will get worse is the device most able to help us make the right decisions. A recent prospective observational study 22 and a large randomized controlled clinical trial 23 both showed that over two thirds of the variance in rates of visual field progression remained unexplained by IOP alone, making this a poor predictive feature used in isolation. However, both studies showed that the ORA derived IOPcc was superior to GAT in predicting rates of glaucoma progression.…”
mentioning
confidence: 99%